Experimental and statistical study of the effect of temperature and waste ratio on the mechanical properties and cost of polystyrene polypropylene plastic blends. Issue 6 (June 2020) - Almishal, Saeed Sameer Ibrahim; Mohamed, Tamer A.; Shazly, Mostafa
Abstract: Since most plastics are not biodegradable, plastic recycling is the main part of global efforts to reduce plastic in the waste stream. Sorting of plastics imposes lots of difficulties which can be avoided by introducing plastic blends. This paper starts by reviewing the recent attempts to study plastic blends. Accordingly, the purpose of this study is to analyze experimental results and apply statistical measures using ANOVA to study the effect of increasing the waste ratio that contains both waste polystyrene and polypropylene on the mechanical properties of pure polystyrene when injected at different temperatures. Cost is taken as a response factor to analyze whether the degradation of mechanical properties is justified by a decrease in cost. As expected, cost dramatically decreases with increasing the waste ratio at any temperature. Increasing the waste ratio resulted in better mechanical properties with a maximum at a 30% waste ratio at 200 °C and 220 °C. This paper ends with a multi-objective optimization analysis that helps decision-makers optimize the properties needed of the studied plastic blend by controlling both the temperature and waste ratio. Abstract : Mechanical Engineering; Materials Characterization; Manufacturing Engineering; Polymers; Mechanical Property; Waste Treatment; plastic blends; recycling; ANOVA; Polystyrene; Polypropylene; waste ratio